An FPGA Implementation of a Polychronous Spiking Neural Network with Delay Adaptation - Wang, Runchun M.; Cohen, Gregory; Stiefel, Klaus M.; Hamilton, Tara J.; Tapson, Jonathan C.; van Schaik, André (Frontiers in Neuroscience, 2013)
We present an FPGA implementation of a re-configurable, polychronous spiking neural network with a large capacity for spatial-temporal patterns. The proposed neural network generates delay paths de novo, so that only connections that actually appear in the training patterns will be created. This allows the proposed network to use all the axons (variables) to store information. Spike Timing Dependent Delay Plasticity is used to fine-tune and add dynamics to the network. We use a time-multiplexing approach allowing us to achieve 4096 (4k) neurons and up to 1.15 million programmable delay axons on a Virtex 6 FPGA. The testing results show that the proposed neural network is capable of successfully recalling more than 95% of all spikes for 96% of the stored patterns. The tests also show that the neural network is robust to noise from random input spikes.